Effects of ambient PM2.5 on development of psoriasiform inflammation through KRT17-dependent activation of AKT/mTOR/HIF-1α pathway - Xueliang Wang; Linpeng Niu; Aijuan Kang; Yaxian Pang; Yaling Zhang; Wenqing Wang; Yan Zhang; Xiaoyan Huang; Qingping Liu; Zihan Geng; Liyi He; Yujie Niu; et al. (Ecotoxicology and Environmental Safety, 2022)
Exposure to fine particulate matter (PM2.5) has significant effects on human skin health, mainly disrupting skin homeostasis and accelerating aging. To date, the effects of PM2.5 on psoriasis (PSO) have not been elucidated. An ambient particulate matter exposed and well characterized imiquimod (IMQ)-induced psoriasis mouse model was established. Thirty male C57BL/6 mice aged 8 weeks were randomly divided into three groups: filtered air (FA) group (Control group), PSO+ FA group and PSO + PM2.5 group. A KRT17 knockdown (KRT17-KD) mouse model was simultaneously established by subcutaneously injecting KRT17-KD lentivirus. Forty male C57BL/6 mice were randomly divided into four groups: PSO + FA + KRT17-RNAi negative control lentivirus (KRT17-NC) group, PSO+ FA+ KRT17-KD group, PSO + PM2.5 + KRT17-NC group and PSO + PM2.5 + KRT17-KD group. PM2.5 exposure continued for 8 weeks. Psoriasis was induced by topically applying IMQ on the dorsal skin of the mice for 6 days during week 8. Morphometric and histological analyses were performed to investigate the changes in psoriatic lesions. Differentially expressed genes and enriched pathways were explored using bioinformatics analysis and showed that KRT17 gene and the vascular endothelial growth factor receptor signaling pathway were associated with psoriasis. HaCaT cells were stimulated with interleukin-17A and infected with KRT17-KD lentivirus to establish an in vitro KRT17 knockdown psoriasis cell model. Notably, PM2.5 exposure increased the expression of KRT17 protein and activated AKT/mTOR/HIF-1α signaling pathway in vivo. Moreover, specific agonist of AKT (740Y-P) reversed the decreased neovascularization induced by KRT17 knockdown through AKT/mTOR/HIF-1α signaling pathway in vitro. Consequently, PM2.5 exposure could promote the development and progression of psoriasis through KRT17-dependent activation of AKT/mTOR/HIF-1α signaling pathway.